Implementation and assessment of a prevention with positives intervention among people living with HIV at five hospitals in Thailand. - Benjamas Baipluthong; Thanomsak Anekthananon; Warangkana Munsakul; Supunnee Jirajariyavej; Suvanna Asavapiriyanont; Ubonsri Hancharoenkit; Anuvat Roongpisuthipong; Sarika Pattanasin; Michael Martin; Lisa Guntamala; Rangsima Lolekha (PLoS ONE, 2017)
Background We implemented a hospital-based prevention with positives (PwP) intervention among people living with HIV (PLHIV) that included HIV transmission risk screening, short HIV prevention messages, family planning, HIV disclosure counseling, and partner HIV testing at five hospitals in Thailand. We assessed changes in sexual risk behaviors among PLHIV who received the PwP services at the hospitals. Methods From January 2008-March 2009, we systematically selected a subset of PLHIV receiving care at the five hospitals to offer participation in the PwP intervention. We collected demographic, risk behavior, and laboratory data using a standardized questionnaire. We analyzed data from PLHIV who completed at least four visits, using generalized estimating equations to identify baseline participant characteristics that were associated with adopting sexual practices less likely to be associated with HIV transmission during follow-up. Results A total of 830 PLHIV were interviewed and 756 (91.1%) completed four visits. The median age of these 756 participants was 37 years, 400 (52.9%) were women, and 475 (62.8%) had a steady partner. At baseline, 353 (74.3%) of the steady partners had been tested for HIV and 132 (37.4%) had tested negative. Among the 756 PLHIV, 427 (56.5%) reported having sex in the 3 months before enrollment and 413 (54.6%) in the 3 months before the fourth visit. The proportion reporting having vaginal or anal sex without a condom decreased from 20.8% at baseline to 5.1% at the fourth visit (p<0.001). Factors associated (p<0.05) with abstinence or 100% condom use at follow-up visits included: completing ≥ two visits, being diagnosed with HIV for longer than 3 months, and receiving HIV prevention messages from a doctor (versus a nurse or counselor). Conclusion Safe sex behaviors increased among PLHIV receiving PwP services, suggesting that expansion of hospital-based PwP services may reduce the number of new HIV infections in Thailand.